A theory of change to reverse the current Mexican freshwater fish extinction crisis - Contreras-MacBeath, Topiltzin; Mejia Mojica, Humberto; Rivas González, Juan Manuel (Frontiers in Environmental Science, 2022)
Freshwater ecosystems are considered amongst the most imperiled on earth, since rivers, lakes, wetlands, and other surface waters receive most of the impacts from unsustainable human activities. This has had measurable impacts on freshwater species, and more specifically on freshwater fishes, as data from the Red List show that 23.5% of the 11,937 freshwater fish species evaluated so far, are classified as threatened. Mexico is not exempt from this situation, as a recent report demonstrates that 39.9% of Mexican freshwater fishes are threatened, and there are 21 lost species (extinct + extinct in the wild), the highest number for any country or region of the world. Here we develop a Theory of Change (ToC) to guide management interventions when seeking to prevent further freshwater fish extinctions in Mexico and reversing the current extinction crisis. We describe four thematic areas of intervention: (1) restoration and reintroduction aimed at eight extinct in the wild and four regionally extinct species, (2) conservation management prioritizing 39 critically endangered species, distinguishing between those inhabiting protected areas, water parks, and those with no management nor protection, (3) explorations to find eight possibly extinct species, and (4) communication and outreach to gain support for conservation interventions. The framework has been developed as a tool for conservation advocates and policymakers to implement and monitor change that prevents extinctions, but also to seek and attract funding. It is also meant to guide different levels of government in setting priorities for conservation interventions.